Analysis of Affixes in the Lyric Song "For the Rest of My Life" by Maher Zain - Muhammad Roihanul Ghozali; Norma Ita Sholichah (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to analyze the use of affixation in the song lyrics For the Rest of My Life by Maher Zain. The focus is on identifying the types of affixes—particularly prefixes and suffixes—and understanding their morphological functions in the lyrical context. A qualitative descriptive method is employed, using morphological theory to examine how affixation contributes to word formation and meaning-making in the lyrics. The results reveal that suffixes are significantly more dominant than prefixes. Suffixes such as -ing, -ed, -s, -es, and -ly appear frequently and serve various grammatical purposes, including indicating verb tenses (such as the present participle and past tense), forming plural nouns, and transforming adjectives or adverbs. These suffixes also play a role in changing word classes, for instance, from verbs to nouns or adjectives to adverbs. This shift enriches the lexical variety and enhances the emotional and poetic expression within the song. Interestingly, the research found no use of prefixes in the lyrics, which may reflect stylistic or rhythmic choices by the songwriter. The absence of prefixes may also suggest a preference for linguistic simplicity and lyrical flow, which are important in songwriting to maintain musicality and ease of listening. The findings highlight how affixation contributes not only to the grammatical structure but also to the aesthetic and expressive quality of the lyrics. The use of affixes enhances the clarity of meaning and allows the songwriter to convey emotions effectively through carefully chosen morphological forms. Moreover, this study contributes to the field of morphological analysis in linguistics, particularly in musical and literary texts. It is expected that the research will serve as a valuable reference for students, educators, linguists, and anyone interested in exploring the intersection between language, music, and literature.